Manajemen Sumberdaya Guru di Pondok Pesantren Bustanul Arifin Kecamatan Kuaro Kabupaten Paser Kalimantan Timur dalam Meningkatkan Profesionalisme Guru - Ujang Sumarna; Moch. Tolchah; Din M. Zakariya (Dinasti Review, 2024)
Teacher resource management adopts a strategic approach to enhance teachers' skills and motivation while managing and organizing their resources to achieve institutional goals. Professional teachers are considered to have specific abilities and expertise in the field of education, enabling them to perform their duties and functions optimally. This research aims to explain how human resource planning and development at Pondok Pesantren Bustanul Arifin can enhance teacher professionalism. The method used is a qualitative descriptive approach with data collection techniques through interviews, observations, and documentation. Data analysis is conducted through stages of data collection, data presentation, and drawing conclusions, using source triangulation for data validation. Research findings show that the school principal at Pondok Pesantren Bustanul Arifin organizes planning, implementation, and evaluation of work programs aimed at improving the quality of educators, including developing semester programs with teachers, training, and delegating teachers in workshops periodically. Every year, deputy principals organize activity plans and budgets related to the curriculum and teacher development. Furthermore, training and development aim to unearth and develop teachers' potential to enhance academic, managerial, and behavioral competencies contributing to school progress. Teachers must continue to enhance their knowledge and skills as they are agents of learning and role models for their students.